Faktor-Faktor yang Memengaruhi Hubungan Kelekatan Ibu terhadap Janin dalam Kandungan - Sulistami Prihandini; Linda Primana (Faculty of Psychology Universitas Gadjah Mada, 2019)
Based on previous studies, it has been known that maternal fetal attachment, significantly affects the health of mother's pregnancy and the optimization of infant development. This literature review wants to find out what factors influence maternal fetal attachment. After extracting 343 articles, 9 articles were discussed. As the result, there are several demographic and psychological variables that significantly influence maternal fetal attachment. Demographic variables that influence maternal fetal attachment are age, maternal education, socioeconomic status, number of children, type of pregnancy (parity), pregnancy plan, previous pregnancy, impaired pregnancy and gestational age. On the other hand, psychological influences on maternal and fetal attachment are depression, social support, family atmosphere, anxiety, self-compassion, and pregnant mother's ability to be close and trusting to other people.